A Rare Case of Hemophagocytic Lymphohistiocytosis in an Adult with Diffuse Large B-Cell Lymphoma - Chimezie Mbachi; Rita Igwilo; Estefania Flores; Ezekiel Chukwujindu; Benjamin Mba (Case Reports in Hematology)
A 71-year-old Indian female presented with a 3-month history of weight loss and fatigue. Further review confirmed a histological diagnosis of diffuse large B-cell lymphoma. Although bone marrow analysis did not reveal hemophagocytosis, she had some clinical and laboratory pointers to hemophagocytic lymphohistiocytosis (HLH). Her clinical state deteriorated rapidly with development of acute respiratory distress syndrome, diffuse alveolar hemorrhage, and subsequently death.